What is technology education? - Dakers, John R. (LUMAT: International Journal on Math, Science and Technology Education, 2024)
The trouble with answering the question ‘What is technology education?’ is that there is no precise and well-defined answer. This is attributable, in one important respect, to the breadth of subject domains that exist in technology education today. These vary across the world but may include woodwork, metalwork, working in plastics, technical drawing or graphic communication, CAD, electronics, pneumatics, mechanics, design or learning about the concept of becoming technologically literate. Each of these subject domains tends to be taught independently from one another and assessed likewise. You cannot teach and assess technical drawing in a woodwork or metalwork classroom setting. This particular issue has now become further confused with the introduction of STEM education.